Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1128/aem.71.1.159-168.2005
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of Animal and Human Glycopeptide-Resistant Enterococci on Two Norwegian Poultry Farms Formerly Exposed to Avoparcin Is Associated with a Widespread Plasmid-Mediated vanA Element within a Polyclonal Enterococcus faecium Population

Abstract: The evolutionary processes responsible for the long-term persistence of glycopeptide-resistant Enterococcus faecium (GREF) in nonselective environments were addressed by genetic analyses of E. faecium populations in animals and humans on two Norwegian poultry farms that were previously exposed to avoparcin. A total of 222 fecal GREF (n ‫؍‬ 136) and glycopeptide-susceptible (n ‫؍‬ 86) E. faecium (GSEF) isolates were obtained from farmers and poultry on three separate occasions in 1998 and 1999. Pulsed-field gel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
65
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(77 citation statements)
references
References 61 publications
7
65
1
Order By: Relevance
“…Difficulties also arise from the different methods used for this purpose, which complicates comparison among studies (14,44,45). Tn1546 may be located in conjugative plasmids (14,20,25,43,47) or in larger composite transposons, as documented for isolates with chromosomally located vanA (15). Horizontal transfer of conjugative plasmids containing Tn1546 seems to have played a relevant role in the recent increase of VRE in Portugal, as vanA was plasmid located in most VRE isolates studied and specific plasmids containing the most prevalent Tn1546 variants were identified in representative distinct clones collected from different cities and years (13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Difficulties also arise from the different methods used for this purpose, which complicates comparison among studies (14,44,45). Tn1546 may be located in conjugative plasmids (14,20,25,43,47) or in larger composite transposons, as documented for isolates with chromosomally located vanA (15). Horizontal transfer of conjugative plasmids containing Tn1546 seems to have played a relevant role in the recent increase of VRE in Portugal, as vanA was plasmid located in most VRE isolates studied and specific plasmids containing the most prevalent Tn1546 variants were identified in representative distinct clones collected from different cities and years (13).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the role of prevalent and persistent E. faecalis and E. faecium strains in the maintenance of the resistance by acquiring different genetic elements must not be underestimated, highlighting the complex epidemiology associated with successful spread of multidrug-resistant enterococci, as illustrated in Poland and the United States, where both successful plasmids and prevalent clones contributed to endemicity (11,21,22). Plasmid persistence has been described in areas with both high and low antibiotic selective pressure, as in the United States versus Norway or Denmark, suggesting that factors other than antibiotic pressure might be important in VRE maintenance and epidemiology (17,20).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the sequence alignment of the axe-txe, par, parDE, ccd, mazEF, relBE, higBA, vagCD, and phd-doc TA genes in the National Center for Biotechnology Information database, pairs of fixed primers specific to each TA system were designed to amplify internal fragments with sizes ranging from 456 bp to 1.04 kb. The sequence of primers to amplify the --gene system was identical to those reported (44). The sequences of all primers are listed in SI Table 4. PCR amplification was performed in a final volume of 100 l containing 1-3 l of purified total DNA or plasmid DNA, 1ϫ PCR buffer (20 mM Tris⅐HCl/50 mM KCl, pH 8.4), 1.5 mM MgCl 2 , 0.2 mM each deoxynucleoside triphosphate, 0.5 M each primer, and 2.5 units of Taq polymerase (Invitrogen, Carlsbad, CA).…”
Section: Isolation Of Plasmids Encoding Vancomycinmentioning
confidence: 97%
“…Our recent study of GRE persistence on two Norwegian farms previously exposed to avoparcin concluded that the GRE population in poultry is heterogeneous with a common plasmid-borne Tn1546 element shared by distinct genetic lineages (21). It was suggested that Tn1546 might be stably maintained through physical linkage to a putative pRE25-related postsegregational killing (PSK) system (21).…”
mentioning
confidence: 99%